The social consequences of organized crime in Italy - Pierfrancesco Rolla; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Organized crime affects security, development, and democracy worldwide, but not much is known about its social consequences. We study how exposure to the presence of organized crime groups shapes the social capital of Italian citizens, including political participation, civic engagement, and institutional and interpersonal trust. To address this question, we first leverage a survey of almost 800,000 respondents on social capital and exposure to organized crime conducted in Italy between 2000 and 2018. Second, we compile data on social capital and related variables between 1861 and 2020 in the Italian region of Apulia to exploit the unexpected and exogenous arrival, in the 1970s, of organized crime in the region, where no groups had been present before. We compare levels of social capital in Apulia with a synthetic control of regions which were not notably exposed to the presence of organized crime groups. Results from both exercises show that exposure to organized crime reduces political participation, institutional and interpersonal trust and has mixed effects on civic engagement. Using a mediation analysis leveraging both quantitative and qualitative evidence, we show that the negative effects of organized group presence on political participation and trust are largely explained by disinvestment in social capital by those exposed to the presence of criminal groups due to psychological factors (fear and resignation) and frustration with lack of state capacity to deal with the groups.
Keywords: E26; H00; K42; 330; organized crime; gangs; Mafia; social capital; Italy